Dynamic time warp of emotions in patients with cutaneous T-cell lymphoma treated with corticosteroidsCapsule Summary - Anne-Sophie C.A.M. Koning, MSc, PhD; Rosanne Ottevanger, MD; Maarten H. Vermeer, MD, PhD; Onno C. Meijer, MSc, PhD; Erik J. Giltay, MD, PhD (Elsevier, 2024)
Background: A substantial number of patients treated systemically with synthetic glucocorticoids undergo emotional disturbances during treatment. Patients with cutaneous T-cell lymphoma frequently experience skin inflammation and itching and often require glucocorticoid treatment. Objective: This case-series study aimed to examine how emotional and skin-related symptoms interact throughout glucocorticoid treatment. Methods: Five cutaneous T-cell lymphoma patients undergoing systemic glucocorticoid treatment completed daily ecological momentary assessments for on average 30 assessments. Fluctuations in their emotions and symptoms were analyzed using undirected and directed dynamic time warp analyses, and were visualized in symptom networks. Results: Toward the end of the glucocorticoid treatment, a decline was found in positive psychological symptoms. Idiographic dynamic time warp analyses revealed highly variable symptom networks. Directed time-lag group-level analyses revealed irritability, enthusiastic, and excited as variables with highest outstrength, in which mainly decreasing levels of positive emotions were associated with a higher likelihood of experiencing increases in itchy skin and skin problems the next day. Conclusion: The end of glucocorticoid treatment, potentially via the induction of hypocortisolism, seems to coincide with decreased energy, motivation, and enthusiasm. Itch and skin problems could be a consequence of low-positive emotions the day before.